The Effectiveness of Fragrant Pandan Leaves Ethanol Extract in Reducing Cholesterol Levels In High-Fat Diet-Induced Rats - Sukanty, Ni Made Wiasty; Ariani, Farida; Yunita, Lina (Biology, Medicine, & Natural Product Chemistry, 2024)
Coronary heart disease was the primary cause of death in Asia in 2019. Indonesia is the country with the highest increase in cholesterol levels in Southeast Asia. One of the causes of coronary heart disease is consuming foods high in cholesterol. The commonly given therapy is simvastatin. However, long-term use of simvastatin can cause side effects, so it is necessary to use other alternatives. Pandanus ammaryllifolius also known as fragrant pandan is a plant that is often found in Indonesia and is used in the culinary industry. This study aims to test the effectiveness of fragrant pandan leaves ethanol extract (FPLEE) in reducing cholesterol levels in rats. A total of 30 rats were split into six groups (NC, C+, C-, T1, T2, and T3) and induced on a high-fat diet, except the NC group for 14 days. For the next 14 days, C+ was given a high-fat diet, C- was given simvastatin, T1, T2, and T3 were respectively given FPLEE doses of 8, 16, and 32 mg/200 g BW/day. Next, cholesterol levels were measured. The results of cholesterol levels were tested statistically using One-Way ANOVA and post hoc LSD tests with a = 0.05. There is no substantial difference between NC, C-, and T2. There is a significant difference between T1 and C+ with a higher T1 value. Meanwhile, for T3, there is no significant difference between T3 and NC, C-, and C+. Thus, the most effective dose for reducing cholesterol levels is 16 mg/200 g BW/day.